A new topical transdermal sildenafil gel formulation to improve skin flap viability in a rabbit model - Liang, Kho Swee (2018)
Skin flap survival is one of the most important outcomes in reconstructive surgery. Various applications of pharmacological agents with different dosing regimens have been shown to improve flap survival experimentally with varying degrees. This study aimed to produce an effective topical gel formulation of sildenafil citrate for the improvement of skin flap survival. Characterization of physicochemical properties and basic stability tests were carried out on the gel formulation. Skin flaps (14 cm x 5 cm) based on superficial inferior epigastric vessels was designed and raised on nine New Zealand White rabbits (weight range 2.5-3.2 kg). An aliquot of 1 ml gel consisted of sildenafil citrate (3 mg) was applied immediately post-surgery to the distal half of the flap in treatment group (n = 3) while 1 ml gel without sildenafil was applied to vehicle control group (n = 3), and none was applied to controls (n = 3). Blood perfusion at the flap distal end and mean necrotic index of the skin flaps were measured continually for 10 days after the flap surgery using laser Doppler flowmetry (LDF) and 2-plane planimetry, respectively. Necrotic index (mean ± standard deviation) in the treatment group was significantly lower compared to control and vehicle control group (Treatment group, 0.25 ± 0.43% vs. vehicle control 5.41 ± 3.50% vs. control 5.41 ± 1.53%; p = 0.017). Early blood perfusion improvement was observed in the treatment group with significant increase seen at flap distal end on the first 24 hours post-surgery (p < 0.001). Ex vivo drug release data of the sildenafil gel across rabbit skin (n = 3) showed that more than half of the drug content were released after six hours (58.03%) and 95.84% of the drug were released after 24 hours. The drug release in the first 24 hours was found to follow the first-order kinetic model, and the release exponent, n, was found to be greater than 1.0 using the Korsmeyer-Peppas equation. Both kinetic analyses showed that the current sildenafil gel formulation demonstrated controlled release properties for extended drug release. In conclusion, this study demonstrated that single application of the current gel formulation of sildenafil (3 mg/ml) significantly increased microcirculatory blood perfusion at the flap distal end and improved skin flap survival in rabbits.